PEMBAYARAN UPAH BURUH PERUSAHAAN YANG PAILIT AKIBAT PANDEMI COVID-19 - Siti Afiyah (LPPM UNISDA, 2021)
As a result of the Covid_19 Pandemic which resulted in the very decline of the community's economy from the top to the bottom. Workers are one of the parties when a company goes bankrupt, but often in the bankruptcy process the constitutional rights of workers are ignored. Indonesia is a state of law (rechtstaat), not based on power (machtstaat)